Speed agility trends in children according to growth: A new approach to evaluate speed agility in children - Matteo Giuriato; Roberto Codella; Nicola Lovecchio; Vittoria Carnevale Pellino; Matteo Vandoni; Alan M. Nevill (Annals of Human Biology, 2021)
Background Speed agility is considered as the whole assessment of speed of movement, agility and coordination. The 10x4m test has been broadly used to evaluate physical fitness and overall health in children of developmental ages. A myriad of studies have investigated the ecology of speed agility (SA). However, body dimensions are rarely appraised, and this is a weakness because body shapes are affected by growth. Aim This study aimed to model SA-specific allometric equations, and develop an approach objectively predictive for performance while controlling for maturity through age at peak height velocity (agePHV). Subjects and methods A total of 7317 (3627 girls) children aged 8–11 years were SA-tested. Multiplicative models with allometric body-size components, agePHV, and categorical differences, were implemented to evaluate SA performance. Results Model 1 accounted for body-size and shape only, whereas Model 2 included agePHV and Model 3 considered standing broad jump (SBJ) as a surrogate marker for explosive strength. An ectomorphic dominance was revealed across all the models. Conclusion The explosive strength resulted in influencing SA per height-to-weight ratio. Further, positive exponent of agePHV suggested that the late maturers were likely to show better SA performances. Predictive equations modelled on developmental factors are fundamental to scrutinise performances as valuable health and fitness outcomes in childhood.